Physiochemical properties of petunia edible flowers grown under saline conditions and their postharvest performance under modified atmosphere packaging and ethanol application - Chrysargyris, Antonios; Tzionis, Andreas; Xylia, Panayiota; Nicola, Silvana; Tzortzakis, Nikos G. (My University, 2019)
BACKGROUND: Edible flowers have both great nutritional value and sensory appeal; however, their shelf-life is limited to a few days because they are highly perishable. RESULTS: The impact of postharvest ethanol (ET) treatment and modified atmosphere packaging (MAP) on the quality and storage of edible flowers collected from short-term salt-stressed plants was tested. Hydroponically grown petunia (Petunia x hybrita L.) plants were subjected to salinity (0–50–100 mmol L –1 NaCl) and harvested flowers were stored for up to 14 days in MAP and/ET vapours. The salinity of 100 mmol L –1 NaCl decreased plant biomass and negatively affected physiological processes as a result of stomata closure. Flower polyphenols, antioxidants, carotenoids and anthocyanins increased with 50 mmol L –1 of NaCl, indicating a higher nutritional value. Short-term exposure of petunia to salinity decreased the flower N, K and Ca concentrations. During storage for 7 days, salinity lead to deteriorated flowers that showed browning as a result of tissue breakdown, whereas CO 2 production and weight loss were unaffected by salinity. After 14 days of storage, salinity decreased flower respiration and increased weight loss, whereas ET application completely destroyed the flowers. Carotenoids and anthocyanins were decreased by a combination of salinity and ET. Petunia flowers revealed the induction of both non-enzymatic (i.e. proline content) and enzymatic (catalase) mechanisms to overcome the stress caused by salinity at harvest stage and/or ethanol at storage. CONCLUSION: The results of the present study demonstrate that a short-stress salinity of 50 mmol L –1 NaCl can be used for petunia growth and also that flowers of nutritional value can be stored for up to 7 days, whereas ET application failed to preserve petunia flowers.
Keywords: Antioxidants; Edible flowers; Ethanol; Hydroponics; Petunia; Shelf-life